2012
DOI: 10.1038/embor.2012.17
|View full text |Cite
|
Sign up to set email alerts
|

TCR‐mediated Erk activation does not depend on Sos and Grb2 in peripheral human T cells

Abstract: Sos proteins are ubiquitously expressed activators of Ras. Lymphoid cells also express RasGRP1, another Ras activator. Sos and RasGRP1 are thought to cooperatively control full Ras activation upon T-cell receptor triggering. Using RNA interference, we evaluated whether this mechanism operates in primary human T cells. We found that T-cell antigen receptor (TCR)-mediated Erk activation requires RasGRP1, but not Grb2/ Sos. Conversely, Grb2/Sos-but not RasGRP1-are required for IL2-mediated Erk activation. Thus, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 24 publications
6
36
1
Order By: Relevance
“…Such observations further point out the potential overlapping role of the Sos isoforms during the latter stages of T-cell development, although they could also be a consequence of the disruption or early thymocyte maturation occurring in the DKO mice. The data from our present BM transplantation experiments, together with the recent demonstration of Sos-independent, TCR-mediated Erk activation in peripheral human T cells (35), favor the second possibility, although a more definitive mechanistic answer requires further investigations. Similarly, analysis of the distribution of maturation-associated B-cell subsets in the spleen and PB also showed that only combined disruption of the two Sos proteins leads to a clear alteration of all subsets of mature B lymphocytes but marginal-zone B cells, except for slightly decreased BT2 counts in the spleens of Sos1 and Sos2 single-KO mice.…”
Section: Discussionmentioning
confidence: 64%
“…Such observations further point out the potential overlapping role of the Sos isoforms during the latter stages of T-cell development, although they could also be a consequence of the disruption or early thymocyte maturation occurring in the DKO mice. The data from our present BM transplantation experiments, together with the recent demonstration of Sos-independent, TCR-mediated Erk activation in peripheral human T cells (35), favor the second possibility, although a more definitive mechanistic answer requires further investigations. Similarly, analysis of the distribution of maturation-associated B-cell subsets in the spleen and PB also showed that only combined disruption of the two Sos proteins leads to a clear alteration of all subsets of mature B lymphocytes but marginal-zone B cells, except for slightly decreased BT2 counts in the spleens of Sos1 and Sos2 single-KO mice.…”
Section: Discussionmentioning
confidence: 64%
“…We have also described digital ERK activation patterns for TCR-stimulated peripheral T cells in the past (10). Recently, SOS1 has been suggested to be of more limited importance in TCR-induced ERK activation in peripheral T cells (78), although FACS patterns of ERK activation were not examined in this study. Future studies should address the question of whether differences in SOS-mediated ERK activation with the various experimental models are a reflection of compensatory mechanisms or due to the developmental stage of the cell population in the analysis.…”
Section: Fig 10mentioning
confidence: 98%
“…RasGRP1 will in turn enhance the generation of active Ras leading to the activation of the Raf-Mek-Erk cascade. However, for sustained Ras signaling and T-cell activation the activity of Sos1 is also required (Roose et al, 2007;Das et al, 2009;Warnecke et al, 2012;Poltorak et al, 2014).…”
Section: Diversification Of the Signal: The Lat Signalosomementioning
confidence: 99%